Analisis Penerapan Literasi Digital dalam Bermedia Sosial di Kalangan Generasi Z - Rida Ristiani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Social media is now an important part of modern life, but the improper use of such platforms has the potential to cause various problems, such as the spread of fake news, online harassment, and addiction. This research aims to see how Generation Z uses digital literacy in social media. Generation Z grew up in the digital age, and has a unique way of interacting with technology. This study uses a qualitative approach through interviews, the subjects are high school students between the ages of 15-17 years. This study was conducted in May 2025. This study proposes to increase the digital literacy of Gen-Z so that social media is used wisely and responsibly, because there are still many aspects that must be improved, including the ability to verify information and understand the ethical consequences of using social media.